Targeting Ras-Driven Cancer Cell Survival and Invasion through Selective Inhibition of DOCK1 - Hirotada Tajiri (Cell Reports, 2017)
Summary: Oncogenic Ras plays a key role in cancer initiation but also contributes to malignant phenotypes by stimulating nutrient uptake and promoting invasive migration. Because these latter cellular responses require Rac-mediated remodeling of the actin cytoskeleton, we hypothesized that molecules involved in Rac activation may be valuable targets for cancer therapy. We report that genetic inactivation of the Rac-specific guanine nucleotide exchange factor DOCK1 ablates both macropinocytosis-dependent nutrient uptake and cellular invasion in Ras-transformed cells. By screening chemical libraries, we have identified 1-(2-(3′-(trifluoromethyl)-[1,1′-biphenyl]-4-yl)-2-oxoethyl)-5-pyrrolidinylsulfonyl-2(1H)-pyridone (TBOPP) as a selective inhibitor of DOCK1. TBOPP dampened DOCK1-mediated invasion, macropinocytosis, and survival under the condition of glutamine deprivation without impairing the biological functions of the closely related DOCK2 and DOCK5 proteins. Furthermore, TBOPP treatment suppressed cancer metastasis and growth in vivo in mice. Our results demonstrate that selective pharmacological inhibition of DOCK1 could be a therapeutic approach to target cancer cell survival and invasion. : Tajiri et al. find that the Rac-specific guanine nucleotide exchange factor DOCK1 is required for oncogenic Ras-driven nutrient uptake and cellular invasion. Through chemical library screening, they identify TBOPP as a DOCK1-selective inhibitor that suppresses growth and metastasis of Ras-transformed cancer cells in vivo. Keywords: Ras, cancer cell survival, cancer cell invasion, metabolism, macropinocytosis, DOCK1, small-molecule inhibitor